The Career Decisions of Young Men - Keane, Michael P.; Wolpin, Kenneth I. (Journal of Political Economy, 1997)
This paper provides structural estimates of a dynamic model of schooling, work, and occupational choice decisions based on eleven years of observations on a sample of young men from the 1979 youth cohort of the National Longitudinal Surveys of Labor Market Experience (NLSY). The authors find that a suitably extended human capital investment model can in fact do an excellent job of fitting observed data on school attendance, work, occupational choices, and wages in the NLSY data on young men and also produces reasonable forecasts of future work decisions and wage patterns. Copyright 1997 by the University of Chicago.